Building a Comprehensive Trust Evaluation Model to Secure Cloud Services From Reputation Attacks - Salah T. Alshammari; Muna Al-Razgan; Taha Alfakih; Khalid A. AlGhamdi (IEEE Access)
Data owners can store extensive data in a flexible and cost-efficient manner by utilizing cloud data storage. Thus, the number of online cloud service providers and their users have undergone a substantial increase. A significant concern in the field of cloud computing is the security and confidentiality of data. A cryptographic access control technique can be used to guarantee data privacy, which prevents unauthorized access and allows only authorized users to access the data. Nevertheless, the trust issue is not fully addressed in this kind of cryptographic approach. The study primarily aims to identify a solution that effectively addresses the trust issues within access control methods, thereby reducing the security risks associated with cloud storage systems. This, in turn, enhances the quality of decisions made by data owners as well as cloud operators. In this paper, we proposed integrating task-role-based access control (T-RBAC) as a new cloud access control model with a comprehensive trust model using various criteria to offer high security for cloud storage systems, with taking flexibility into consideration. There are trust-based systems integrated with various existing access control models in cloud computing; however, these models do not provide accurate trust value computations, and may still be at risk of certain security threats. Hence, these threats can be eliminated through an accurate trust-based T-RBAC model.